Caracterização morfológica e acústica de populações de Crossodactylus Duméril & Bibron, 1841 (Anura, Hylodidae) : implicações taxonômicas e distribuição = Morphological and acoustic description of Crossodactylus Duméril and Bibron, 1841 (Anura, Hylodidae) populations : taxonomic status and distribution - Vidigal, Izadora, 1990- (2017)
Orientador: Ariovaldo Antonio Giaretta